The Effect Of E-service quality, E-trust, and Price on Customer E-Loyalty mediated by Customer E-Satisfaction on Gen Z user of Lazada Application in Padang City: Pengaruh E-service quality , E-trust Dan Price Terhadap Customer E-Loyalty Yang Dimediasi Oleh Customer E-Statisfaction Pada Gen Z Pengguna Aplikasi Lazada di Kota Padang - Fira Rahmadani; Vidyarini Dwita (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research was conducted with the aim of analyzing how electronic service quality, electronic trust, price influence customer loyalty, with customer satisfaction as a mediator in the Lazada application. The subjects of this research are Gen Z in Padang City. The sampling technique uses purposive sampling. The number of samples used was 180 respondents. Data was collected through a questionnaire with a Likert scale, then analyzed using SmartPLS 4.1 software. The results of this research show that electronic service quality, electronic trust, and price have a significant effect on electronic customer satisfaction and loyalty. However, electronic trust does not have a significant effect on electronic customer loyalty. E-customer satisfaction mediates the relationship between E-service quality, E-trust, price and e-customer Loyalty.